Influence Openness To Experience Against Organizational Citizenship Behavior Through Job Satisfaction as an Intervening Variable (At the Regional Secretariat Office of Bulukumba Regency) - Nurdin Brasit; Fauziah Umar; Riswandi Raja (Scientia integritas Utama, 2023)
The Bulukumba Regency Regional Secretariat Office is an organizational body or agency that provides administrative office services. This institution has a vision, primarily for the people of Bulukumba, who are historical and foremost via optimizing the potential of the region by boosting the people's economy based on democratic and religious government. The goal of this study was to evaluate and assess the effect of Openness to Experience on Organizational Citizenship Behavior (OCB) using Job Satisfaction as an intervening variable. This form of research employs quantitative methods. The Regional Secretariat Office provided a sample of 153 respondents for this study. In this study, the measurement scale is a Likert scale. The traditional assumption test, simple regression analysis, and path analysis were employed in this study with the help of IBM SPSS 21 Statistics. The study's findings indicate that openness to experience has a positive and significant effect on job satisfaction; openness to experience has a positive and significant effect on organizational citizenship behavior (OCB); and job satisfaction has a positive and significant effect on organizational citizenship behavior (OCB). Job satisfaction as an intervening variable is significant to organizational citizenship behavior (OCB).